AN EPIDEMIOLOGICAL STUDY OF COVID-19 CASES ADMITTED IN A DEDICATED COVID HOSPITAL DURING SECOND WAVE OF CORONA PANDEMIC IN CENTRAL INDIA - VK, SHARMA; KULSHRESTHA, ALOK; PAL, VISHNU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to find out any peculiarities in the epidemiological and clinical profiles of COVID-19 cases, admitted in the hospital; which may be useful in management of health services in future. Methods: Retrospective analysis of hospital records of COVID-19 cases admitted from March to May 2021 in our COVID hospital. A total of 1332 hospital case records were analyzed. Results: Out of 1332 admitted COVID-19 cases, 50% were in age group 40–60 years. About 60% cases were male. Symptoms were fever (88.29%), sore throat (70.64%), breathlessness (58.84%), loss of smell (58.82%), pain in abdomen (53%), loss of taste (35.29%), and diarrhea (29.43%). Most cases had multiple symptoms. About 60% cases came in serious condition. About 65% cases needed intensive care unit admission. About 50% cases expired. Conclusions: Only peculiarity noticed in clinical profile was loss of taste and sense of smell in few cases. Preponderance of males in the age group of 40–60 years and high mortality among the admitted cases was only peculiar epidemiological feature.